Counter Electrodes for Quantum‐Dot‐Sensitized Solar Cells. Issue 5 (20th February 2015) - Hwang, Insung; Yong, Kijung
Abstract On the basis of the many advantages of quantum dots (QDs) including multiple exciton generation, high absorption coefficient, and band‐gap energy controllability, quantum‐dot‐sensitized solar cells (QDSSCs) have been studied for a few decades. However, despite the many advantages, improvement in the power‐conversion efficiencies of QDSSCs has been stagnated for a long time. To suggest a breakthrough in this stagnated QDSSC field, counter electrodes (CEs) have been focused on and are introduced in this Review article. Counter electrodes have been paid relatively less attention, whereas QDs and photoanode structures have been intensively studied. Nevertheless, it is an unchanged fact that CEs are also of considerable importance in QDSSCs, as they hold the possibility to enhance the performance of QDSSCs. In this Review, as an introduction, the basic working principles of QDSSCs are covered, and some widely used analytical tools for CEs are discussed, such as current density–voltage measurements, electrochemical impedance spectroscopy, cyclic voltammetry, and Tafel polarization measurements. Then, some interesting representative work on CEs is introduced. Given that various types of CEs exist, categorization of the CEs was conducted as follows: noble metals, metal sulfides, carbon derivatives, conducting polymers, and combinations of these types. With this Review article, it is hoped that insight will be gained to achieve a breakthrough in the stagnant field of QDSSC research.